Role of Immune Cells in Biliary Repair - Lan, Tian; Qian, Shuaijie; Tang, Chengwei; Gao, Jinhang (Frontiers in Immunology, 2022)
The biliary system is comprised of cholangiocytes and plays an important role in maintaining liver function. Under normal conditions, cholangiocytes remain in the stationary phase and maintain a very low turnover rate. However, the robust biliary repair is initiated in disease conditions, and different repair mechanisms can be activated depending on the pathological changes. During biliary disease, immune cells including monocytes, lymphocytes, neutrophils, and mast cells are recruited to the liver. The cellular interactions between cholangiocytes and these recruited immune cells as well as hepatic resident immune cells, including Kupffer cells, determine disease outcomes. However, the role of immune cells in the initiation, regulation, and suspension of biliary repair remains elusive. The cellular processes of cholangiocyte proliferation, progenitor cell differentiation, and hepatocyte-cholangiocyte transdifferentiation during biliary diseases are reviewed to manifest the underlying mechanism of biliary repair. Furthermore, the potential role of immune cells in crucial biliary repair mechanisms is highlighted. The mechanisms of biliary repair in immune-mediated cholangiopathies, inherited cholangiopathies, obstructive cholangiopathies, and cholangiocarcinoma are also summarized. Additionally, novel techniques that could clarify the underlying mechanisms of biliary repair are displayed. Collectively, this review aims to deepen the understanding of the mechanisms of biliary repair and contributes potential novel therapeutic methods for treating biliary diseases.